The role of interpersonal emotional regulation on maternal mental health. (2nd January 2022) - Coo, Soledad; García, Maria Ignacia; Prieto, Fernanda; Medina, Franco
ABSTRACT: Purpose: Symptoms of depression and anxiety during the perinatal period have a negative impact on mothers and their developing children. A significant body of research has demonstrated an association between mental health and both individual and interpersonal emotion regulation. Yet, this association has not been studied during the perinatal period. The aim of this study was to explore the association between emotion regulation, maternal mental health, and interpersonal emotion regulation during the transition to motherhood in a sample of Chilean women. Methods: Women in their third trimester of pregnancy (n = 253) provided self-reports of emotion regulation and symptoms of depression and anxiety during pregnancy and three months postpartum. Additional self-reports of interpersonal emotion regulation were obtained from individuals who were identified as social support persons by these women. Results : Maternal emotion regulation contributed to maternal symptoms of depression and anxiety during pregnancy and after childbirth. The association between emotion regulation and maternal mental health was moderated by specific interpersonal emotion regulation strategies reported by the participant's social support persons. Strategies including modulating the emotional response, situation modification, attentional deployment and cognitive change, modified the association between poor regulation strategies and anxiety symptoms. Also, an infrequent use of these interpersonal emotion regulation strategies strengthened the association between these maternal emotional regulation difficulties and anxiety symptoms. Conclusion: Our findings suggest that interpersonal emotional regulation strategies impact the association of maternal emotional regulation strategies and maternal emotional wellbeing.